The Mediating Role Of Technological Innovation On The Relationship Between Green Supply Chain Management And Social Performance - Alhussain Alsuraihi; Khairul Affeiq Mohd. Noorizam; Ab Rahman Z.; Norailis Ab Wahab; Rosnia Masruki (Universidad Técnica de Manabí, 2024)
Non-Indexed Publication